PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA SISWA KELAS SMK - Ghany, Muhammad Afif Abdul; Fauzi, Dani Ahmad; Kartini, Cucu (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
In Indonesia, interest in reading in all circles is still lacking, especially among students and students who are actually people who are struggling in the world of education. This is because the school community does not understand the benefits of literacy. In addition, there are quite a lot of obstacles that occur during reading activities. Today the government makes a policy to foster a culture of literacy through how to familiarize students with reading for 10-15 minutes before learning is carried out. The main subject of this research is class X students. The formulation of the research problem this time is: 1) How is the influence of GLS in increasing student attention reading? 2) What are the obstacles in literacy? The purpose of this study is to be able to determine the influence and barriers of the GLS program to attend to reading students in vocational schools. The type of research method used is a type of qualitative research. The process of collecting the data used is a questionnaire. The results of this study illustrate that attention or interest in reading students increases this can be seen from the results of questionnaires that illustrate that attention to reading of students increases after the GLS student literacy culture can be improved, their reading activities can be observed, and their reading skills develop well by growing literacy culture in students.